2018
DOI: 10.1002/prep.201800052
|View full text |Cite
|
Sign up to set email alerts
|

Diameter Effect on the Propagation of Curved Detonation Waves in Micro‐Channel Charges Within a Strong Confinement

Abstract: The property of detonation wave propagation in micro‐channel charges is one of the most important research areas in the field of explosives. Based on DSD (Detonation Shock Dynamics) theory and a linear assumption for the streamline deflection angle, this paper proposes a theoretical model for curved detonation wave propagation in cylinder‐type micro‐channel charges within a strong confinement of metal tube. Further, dynamic control equations related to the detonation velocity and charge diameter are deduced, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the one hand, the experimental measurement deviation of the detonation velocity will be greater in the smaller size. The literature [25] indicated that the measuring deviation of detonation range from 3.28 % to 10.40 %. On the other hand, the Lee-Tarver does not completely capture all of energy loss mechanisms reponsible for non-ideal detonation in small diameter charge.…”
Section: Detonation Velocity At Different Charge Diametersmentioning
confidence: 99%
“…On the one hand, the experimental measurement deviation of the detonation velocity will be greater in the smaller size. The literature [25] indicated that the measuring deviation of detonation range from 3.28 % to 10.40 %. On the other hand, the Lee-Tarver does not completely capture all of energy loss mechanisms reponsible for non-ideal detonation in small diameter charge.…”
Section: Detonation Velocity At Different Charge Diametersmentioning
confidence: 99%